A policy analysis of nuclear safety culture and security culture in East Asia : examining best practices and challenges - Trajano, Julius Cesar I. (2020)
This paper conducts a qualitative policy analysis of current challenges to safety culture and security culture in Southeast Asia and emerging best practices in Northeast Asia that are aimed at strengthening both cultures. It analyses lessons, including strengths and limitations, that can be derived from Northeast Asian states, given the long history of nuclear energy in South Korea, China and Japan. It identifies and examines best practices from Northeast Asia's Nuclear Security Centres of Excellence in terms of boosting nuclear security culture and their relevance for Southeast Asia. The paper accentuates the important role of the State in adopting policy and regulatory frameworks and in institutionalising nuclear education and training programmes to deepen the safety-security cultures. Best practices in and challenges to developing a nuclear safety culture and a security culture in East Asia are examined using three frameworks of analysis (i) a comprehensive nuclear policy framework; (ii) a proactive and independent regulatory body; and (iii) holistic nuclear education and training programmes. The paper argues that Southeast Asian states interested in harnessing nuclear energy and/or utilising radioactive sources for non-power applications must develop a comprehensive policy framework on developing safety and security cultures, a proactive regulatory body, and holistic nuclear training programmes that cover both technical and human factors. Such measures are crucial in order to mitigate human errors that may lead to radiological accidents and nuclear security crises. Key lessons from Japan, South Korea and China such as best practices and challenges can inform policy recommendations for Southeast Asia in enhancing safety-security cultures.